The Role Of Islamic Community Figures In Fostering Youth Religious Activities At The Al-Amin Mosque In Kuala Tanjung Village, Sei Suka District, Batu Bara Regency - Sahara, Almiza; Parinduri, Sari Atika; Nasution, Herry Syahbannuddin (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
Community leaders are people who have been trusted by the community because of their good abilities and background. In this case the role of community leaders is closely related to the problem of fostering the religious activities of mosque youth. Because it is used as a coach for religious activities in the community, so here the researcher wants to know what roles are played by community leaders, especially Islamic religious leaders in fostering the religious activities of mosque youth. Adolescence is part of the phase in the process experienced by every human being. Adolescence is also a decisive period because at this time children experience many changes in their psychology and physique. The occurrence of psychological changes causes confusion among adolescents. The reason is because they experience emotional turmoil and mental pressure so that they easily deviate from the rules and social norms that apply in society. Thus, Islamic religious leaders as leaders in society must be able to provide good examples and interactions to direct and provide guidance to adolescents. Social interaction is regulated based on goodness, justice and the common good, not just for a particular person or group. Especially youth in mosques, because the presence of Islamic youth groups in this mosque will greatly assist activities held by religious leaders, to unite youth with the environment.